(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The aim of this research is to study the impact of brand strength on customer loyalty, with a focus on the factors that contribute to building this loyalty. This study emphasizes that a strong brand, high quality, and effective communication are critical factors in building customer loyalty. It also asserts that a brand is not just a name or a logo, but represents the identity and values that distinguish the company in the minds of customers. Customer loyalty is considered a vital element for the sustainability and growth of companies, as it reflects the level of customer commitment to the brand and their preference for it over competitors.